Novel Magnetic Nanostructures 2018
DOI: 10.1016/b978-0-12-813594-5.00005-9
|View full text |Cite
|
Sign up to set email alerts
|

Self-Assembly of Magnetic Iron Oxide Nanoparticles Into Cuboidal Superstructures

Abstract: This chapter describes the synthesis and some characteristics of magnetic iron oxide nanoparticles, mainly nanocubes, and focus on their self-assembly into crystalline cuboids in dispersion. The influence of external magnetic fields, the concentration of particles, and the temperature on the assembly process is experimentally investigated.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
10
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 31 publications
(37 reference statements)
2
10
2
Order By: Relevance
“…Two peaks at scattering vector values of q 1 = 1.47 and q 2 = 2.94 nm –1 display a linear correlation of q 1 / q 2 = 1:2, indicating the formation of a lamellar structure with an interlamellar spacing of d (001) ≈ 4.3 nm (Figure d). This lamellar ordering can be attributed to the crystalline oleic acid in accordance with previous observations, where the crystalline structure formed either by pure oleic acid molecules or by oleic acid ligands on nanoparticle surfaces was reported. ,, Rosenfeldt et al observed a similar sharp Bragg peak at q = 1.41 nm –1 (i.e., d (001) ≈ 4.5 nm) in the SAXS profile of a dilute suspension of oleic acid-capped iron oxide nanocubes in toluene. Interestingly, the SAXS curve of spherical iron oxide nanoparticle suspensions did not exhibit such a peak.…”
supporting
confidence: 89%
“…Two peaks at scattering vector values of q 1 = 1.47 and q 2 = 2.94 nm –1 display a linear correlation of q 1 / q 2 = 1:2, indicating the formation of a lamellar structure with an interlamellar spacing of d (001) ≈ 4.3 nm (Figure d). This lamellar ordering can be attributed to the crystalline oleic acid in accordance with previous observations, where the crystalline structure formed either by pure oleic acid molecules or by oleic acid ligands on nanoparticle surfaces was reported. ,, Rosenfeldt et al observed a similar sharp Bragg peak at q = 1.41 nm –1 (i.e., d (001) ≈ 4.5 nm) in the SAXS profile of a dilute suspension of oleic acid-capped iron oxide nanocubes in toluene. Interestingly, the SAXS curve of spherical iron oxide nanoparticle suspensions did not exhibit such a peak.…”
supporting
confidence: 89%
“…4 . Alternatively, a distribution with discrete δ−peaks can be assumed 5,6 . If no knowledge about the particle distribution function is available, an unprejudiced ansatz can be made in connection with a regularization scheme.…”
mentioning
confidence: 99%
“…Rosenfeldt, S., et al conducted a study where they used sodium-oleate and iron salt to synthesize a metal-oleate precursor. It was found that when using a greater excess of sodium-oleate, the particles would synthesize as cubes instead of spheres like they formed with a smaller excess of sodium-oleate [3]. This is one example of how changing the solvent/concentration can contribute to shape-control synthesis.…”
Section: Methods and Outcomesmentioning
confidence: 99%
“…When particles are a certain shape like cubes, there is more self-assembly than other shapes like a sphere. This increased self-assembly can be used to create networks of nanoparticles that can help fabricate functional devices like catalysts and targeting [3]. Applications of these self-assembled networks include oil spill clean-up, toxic metal removal, and removal of dyes in water [9].…”
Section: Motivationmentioning
confidence: 99%
See 1 more Smart Citation